Pengaruh Corporate Social Responsibility (CSR), Ukuran Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia 2017-2019) - Dinda Nur Khofifah; Vhika Meiriasari; Reny Aziatul Pebriani (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze partially and simultaneously the effect of corporate social responsibility, firm size, and profitability on firm value. The data used comes from the financial statements of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period, totaling 17 companies. Panel data regression is a method used to perform data analysis. This study proves partially show that the variables of corporate social responsibility, firm size and, profitability have a positive effect on firm value. Furthermore, the results of research with the correlation coefficient test (R2) show a value of 0.989788, which means that the relationship between the variables of corporate social responsibility, company size, and profitability to firm value is close, namely 98.97%, the remaining 1.03% can be influenced by other variables not included in this study